A STUDY ON THE EFFECT OF NON-GENETIC FACTORS INFLUENCING BODY WEIGHT IN MECHERI SHEEP - N. Murali; V.B. Raghavendran; R. Venkataramanan; D. Balasubramanian (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Data on 3649 Mecheri sheep, maintained at Mecheri Sheep Research Station, Pottaneri, Salem, India and recorded between 1979 and 2012, were analysed to study the effect of non-genetic factors affecting the body weight and average daily gain from birth to twelvemonths of age. The least squares means for birth weight, 3, 6, 9 and 12 months body weight were 2.31±0.009, 8.71±0.049, 12.27±0.075, 14.80±0.100 and 18.31±0.155 kg respectively. The pre and post-weaning average daily gains were 70.86±0.509 and 32.92±0.494 g and the associated growth efficiencies were 3.80 ± 0.019 and 1.44 ± 0.006, respectively. Males were significantly heavier and had a higher weight gain than females during all stages of growth and their differences tended to increase with age. Highly significant differences (p≤0.01) associated with the year of lambing were observed in body weight and weight gain at different stages of growth. The weight of lambs born during season 2 (November - February) was significantly higher than those born in season 1 (March-October) from birth to nine months of age. A significant difference (p≤0.05) was seen at 12th month body weight of lambs born during season 2. These variations can be correlated with the seasonal changes and fodder availability. Hence, it is necessary to plan the lambing season rationally by controlling the oestrus and mating time.